The Good Guys and the Bad Guys: The Behavior of Lenient and Demanding Translation Evaluators - Conde, Tomás (Meta (Montréal), 2012)
The behavior of demanding and lenient evaluators is analyzed and discussed. Little is known about the process of translation evaluation, specifically on how different types of evaluators perform. The 88 subjects of this study were classified as demanding or lenient on the basis of the average quality judgments they made on 48 translated texts. Their profiles were outlined according to a series of parameters and categories starting from the observation of their products, i.e., the evaluated texts. Lenient evaluators carried out more actions on the text, were fairly product-oriented, showed a fairly steady performance, seemed to be more confident, and were probably more committed to the evaluation assignment they were given in this research. Demanding evaluators intervened less, were usually feedback-oriented, preferred to carry out actions in certain segments and text parts, expressed less certainty, and were possibly more aware of the particular circumstances surrounding the experiment. While demanding evaluators appear better suited for professional environments and advanced level teaching, lenient evaluators seem more suited to research and teaching at initial stages. The present work might pave the way for further research into evaluative profiles.